Pengaruh Pajak Daerah, Belanja Modal, dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Kabupaten/Kota Di Provinsi Bali - Ni Komang Ristia Septiari; Ni Luh Gede Erni Sulindawati; Made Aristia Prayudi (Vokasi : Jurnal Riset Akuntansi, 2026)
This study aimed to examine the partial effects of local taxes, capital expenditure, and intergovernmental transfers on local government financial performance. The research employed a causal associative quantitative approach and used budget and realization data published by the Directorate General of Fiscal Balance (DJPK), derived from the Local Government Financial Statements (LKPD) of regencies and municipalities in Bali Province for the period 2021–2024. The sample consisted of nine regencies/municipalities observed over four years, resulting in 36 observations. The results indicate that (1) local taxes have a significant negative effect on local government financial performance, while (2) capital expenditure have significant positive effects on local goverment financial perfomance, and (3) intergovernmental transfers have significant positive effects on local goverment financial perfomance.